Decision Support System for Evaluating Santri Learning Performance at TPA Nurul Ihsan, Pergam Village - Pidaryani, Pidaryani; Afriansyah, Riki; Pratama, Muhammad Setya (STMIK KHARISMA Makassar, 2025)
This study focuses on the implementation of the Simple Additive Weighting (SAW) method in the student assessment system at Taman Pendidikan Al-Qur’an (TPA) Nurul Ihsan, located in Desa Pergam. The main issue faced by the institution is that the assessment process is still conducted manually and subjectively, making it difficult to produce objective evaluation results. The SAW algorithm is applied to evaluate students based on five main criteria: Daily Scores, Midterm Test (UTS), Final Test (UAS) which include memorization of prayers, selected verses, short surahs, prayer practice, recitation performance, and attitude as well as attendance. Each criterion is assigned a weight according to its level of importance, followed by normalization and preference value calculation to determine student rankings. The system is implemented on a mobile-based platform using the Laravel and Flutter frameworks. The testing results show that the SAW method produces consistent scores with an accuracy rate of 89.03%, categorized as “Very Good” based on User Acceptance Testing (UAT). Therefore, the SAW method is proven to be effective in enhancing the objectivity and efficiency of student assessment at TPA Nurul Ihsan.